Computer programming in primary schools: Swedish Technology Teachers’ pedagogical strategies - Bjursten, Eva-Lena; Nilsson, Tor; Gumaelius, Lena (International journal of technology and design education, 2023)
There is a recognized need for research on how to teach computer programming in primary schools in Sweden grades 4–6 (10–12-year-old pupils). Studies of teaching show the importance of teachers’ knowledge of content and pedagogy and how these two parts affect each other (i.e. pedagogical content knowledge [PCK]). Most teachers in Sweden have little or no formal education in computer programming, the revised Swedish curriculum requires them to teach it. The aim of this study is to explore the pedagogical strategies teachers use when they teach computer programming. Semi-structured interviews were conducted with 14 participants, comprising 12 teachers and 2 teacher trainers. The data were analysed deductively with themes from previous research. The results show that teachers use eight pedagogical strategies, including three new strategies that have been constructed inductively: do-it-yourself, gamification and progression. These eight pedagogical strategies are mostly general, and teachers may be considered regressed experts, as they lack formal training in computer programming. They facilitate learning in a general sense, but, compared to other subjects, their PCK in computer programming is problematized. In-service teacher training is needed to increase content knowledge, thus enabling to develop PCK in computer programming. It would also be fruitful to deepen our knowledge regarding pedagogical strategies in the PCK domain of computer programming.